Recruiting and integrating international high-skilled migrants: towards a typology of firms in rural regions in Germany - Schäfer, Susann; Henn, Sebastian (Journal of rural studies, 2023)
In rural regions in Germany, significant demographic shifts have raised the question as to whether increased employment of international high-skilled migrants can help to address pressing challenges, i.e., a shortage of labor, a lack of corporate internationalization, and reduced innovation activities. While firms play a key role in this context by actively recruiting migrants and harnessing their skills and competences, little is still known about how they differ in harnessing the potential of high-skilled migrants. With this as a starting point, we develop a typology of firms that distinguishes between four types of firms (introverted, absorptive, enthralled, and outgoing firms). Using the example of Thuringia, a predominantly rural federal state in East Germany, and based on a method mix that includes quantitative and qualitative elements, we explore these types in detail, analyze their spatial distribution and discuss options to unlock the potential associated with the employment of international high-skilled migrants.
Gesehen am 24.01.2025
Online veröffentlicht: 1. September 2023